Continental Thermal Blanketing Explains the Compositional Dichotomy of the Diffuse Basaltic Province Across Central‐Eastern Asia - Hong‐Kun Dai; Jian‐Ping Zheng; Qing Xiong; William L. Griffin; Suzanne Y. O’Reilly (Geophysical Research Letters)
Abstract A diffuse magmatic province covering central‐eastern Asia continent displays a compositional transition at 120–100 Ma and probably reflects melting initiation in isotopically enriched lithospheric mantle, followed by melting of the asthenosphere. However, the cause for the transition across such a vast landmass remains poorly constrained. Here, analyses of newly found Chaoge basalts (∼95 Ma, central Asia) and compiled data from across the basaltic province are combined to reveal the factors controlling the basalt dichotomy. The Chaoge basalts are considered to originate from a hot pyroxenite‐bearing asthenosphere with potential temperatures of ∼1,450°C, overlapping the source thermochemical conditions for most post‐transition basaltic rocks. The asthenosphere in 120–100 Ma is suggested to be hotter and to have controlled the compositional transition in the studied basaltic province. We suggest that asthenospheric warming resulted from prolonged continental thermal blanketing and can account for other diffuse igneous provinces with similar compositional variations and tectonic histories.